2023
DOI: 10.1017/cts.2023.36
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an experiential training program in patient-centered outcomes and comparative effectiveness research for diverse researcher communities and health care organizations

Abstract: Background/Objective: The goal of the Patient-Centered Outcomes Research Partnership was to prepare health care professionals and researchers to conduct patient-centered outcomes and comparative effectiveness research (CER). Substantial evidence gaps, heterogeneous health care systems, and decision-making challenges in the USA underscore the need for evidence-based strategies. Methods: We engaged five community-based health care organizations that serve diverse and underrepresented patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 20 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…The 35 included articles were mainly in the United States ( n = 14) [ 16 29 ], Canada ( n = 5) [ 30 34 ], Sweden ( n = 2) [ 35 , 36 ], and in other single locations such as Australia, Brazil, Burundi, India, Kenya, and Nigeria, among others ( n = 14) [ 37 50 ]. Of those included, 16 articles were qualitative studies [ 18 , 20 , 25 , 28 , 31 36 , 44 , 45 , 47 50 ], nine were non-empirical papers [ 19 , 22 , 23 , 37 39 , 41 43 ], four were quantitative studies [ 26 , 27 , 29 , 40 ], and six were mixed methods [ 16 , 17 , 21 , 24 , 30 , 46 ]. Eleven studies reported a population of interest, which were mainly Indigenous groups [ 31 , 34 , 48 ], older adults [ 19 ], patients in patient group programmes [ 21 , 27 ], academic faculty and researchers [ 40 ], and mental health practitioners [ 16 ], among others.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The 35 included articles were mainly in the United States ( n = 14) [ 16 29 ], Canada ( n = 5) [ 30 34 ], Sweden ( n = 2) [ 35 , 36 ], and in other single locations such as Australia, Brazil, Burundi, India, Kenya, and Nigeria, among others ( n = 14) [ 37 50 ]. Of those included, 16 articles were qualitative studies [ 18 , 20 , 25 , 28 , 31 36 , 44 , 45 , 47 50 ], nine were non-empirical papers [ 19 , 22 , 23 , 37 39 , 41 43 ], four were quantitative studies [ 26 , 27 , 29 , 40 ], and six were mixed methods [ 16 , 17 , 21 , 24 , 30 , 46 ]. Eleven studies reported a population of interest, which were mainly Indigenous groups [ 31 , 34 , 48 ], older adults [ 19 ], patients in patient group programmes [ 21 , 27 ], academic faculty and researchers [ 40 ], and mental health practitioners [ 16 ], among others.…”
Section: Resultsmentioning
confidence: 99%
“…The practical activities most frequently mentioned included the development of training programmes [ 17 , 19 , 29 , 35 , 44 ] as the primary focus, followed by community-based and stakeholder workshops [ 32 , 37 , 44 , 45 , 49 ] and the facilitation of online webinars, portal links, discussions, and engagement on social media platforms [ 38 , 41 , 43 , 48 ]. These activities were more common in topics such as community and rural health care [ 17 , 35 , 37 ], and policy research [ 41 , 43 , 45 ], across settings in the US [ 16 , 17 , 19 , 21 , 29 ], Brazil [ 45 ], Sub-Saharan Africa [ 43 ], Canada [ 32 ], Sweden [ 35 ], and the UK [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations